Determination of consistency of concentrated dispersed systems by the method of gravitational penetration - Guts, Viktor; Koval, Olha; Bondar, Svitlana (My University, 2019)
Analytical and experimental studies consistency dispersion systems of the new method – gravitational penetration. Dispersion systems – pate meat products from mechanically separated poultry are being investigated. The consistency was determined by gravity penetration. Penetration indices are determined on the basis of mathematical modeling of indenter motion in the product layer based on second order differential equations of motion. Results and discussion. The proposed method for determining consistency is easy to use. The presented calculus dependencies and mathematical models are based on physical constants, which makes the method of gravitational penetration versatile for wide practical application in estimating the quality of food by the express method. The presented mathematical model obtained based on the secondorder differential equations, suitable for different research and use different designs gravitational penetrometer. To perform a comparative analysis of the consistency of food products obtained from different technological modes or formulations, it is proposed to use a comparative characteristic in the form of a coefficient K. Its value is calculated as the ratio of the depth of immersion of the needle into the product layer when falling penetrometer from one height. The highest rates were pate sample containing 40% of mechanically separated poultry meat and 8% of rice flour, and the smallest, pate sample, containing 30% mechanically separated poultry meat and 10% of rice flour. Conclusion. Defining the method of gravitational рenetration extends the possibility of obtaining accurate results in comparison with the use of existing methods and a priori formulas. Аналітичні та експериментальні дослідження систем дисперсії консистенції методом гравітаційного проникнення. Дисперсійні системи – м’ясні продукти паштету з механічно розділеної птиці. Консистенцію визначали за допомогою гравітаційного проникнення. Індекси проникнення визначають на основі математичного моделювання руху індентора в шарі продукту на основі диференціальних рівнянь руху другого порядку. Представлені залежності обчислення та математичні моделі базуються на фізичних константах, що робить метод гравітаційного проникнення універсальним для широкого практичного застосування при оцінці якості їжі експрес-методом. Представлена математична модель, отримана на основі диференціальних рівнянь другого порядку, придатна для різних досліджень і використання в різних конструкціях гравітаційного пенетрометра. Для проведення порівняльного аналізу консистенції харчових продуктів, отриманих з різних технологічних режимів або рецептур, пропонується використовувати порівняльну характеристику у вигляді коефіцієнта К. Її величина обчислюється як відношення глибини занурення голки у шар продукту при падінні пенетрометра з однієї висоти. Найвищими були показники зразка паштету, що містив 40% механічно відокремленого м’яса птиці та 8% рисового борошна, і найменшими – у зразка паштету, що містив 30% м’яса птиці, механічно відокремленого, та 10% рисового борошна. Метод гравітаційного проникнення розширює можливість отримання точних результатів у порівнянні із застосуванням існуючих методів та апріорних формул.
Keywords: gravity; consistency; food; консистенція; проникнення; сила тяжіння; їжа; penetration; кафедра технології ресторанної і аюрведичної продукції